Pilot investigation of two-stage biofiltration for removal of natural organic matter in drinking water treatment. (January 2017) - Fu, Jie; Lee, Wan-Ning; Coleman, Clark; Meyer, Melissa; Carter, Jason; Nowack, Kirk; Huang, Ching-Hua
Abstract: A pilot study employing two parallel trains of two-stage biofiltration, i.e., a sand/anthracite (SA) biofilter followed by a biologically-active granular activated carbon (GAC) contactor, was conducted to test the efficiency, feasibility and stability of biofiltration for removing natural organic matter (NOM) after coagulation in a drinking water treatment plant. Results showed the biofiltration process could effectively remove turbidity (<0.1 NTU in all effluents) and NOM (>24% of dissolved organic carbon (DOC), >57% of UV254, and >44% of SUVA254 ), where the SA biofilters showed a strong capacity for turbidity removal, while the GAC contactors played the dominant role in NOM removal. The vertical profile of water quality in the GAC contactors indicated the middle-upper portion was the critical zone for the removal of NOM, where relatively higher adsorption and enhanced biological removal were afforded. Fluorescence excitation-emission matrix (EEM) analysis of NOM showed that the GAC contactors effectively decreased the content of humic-like component, while protein-like component was refractory for the biofiltration process. Nutrients (NH4 -N and PO4 -P) supplementation applied upstream of one of the two-stage biofiltration trains (called engineered biofiltration) stimulated the growth of microorganisms, and showed a modest effect on promoting the biological removal of small non-aromatic compositions in NOM. Redundancy analysis (RDA) indicated influent UV254 was the most explanatory water quality parameter for GAC contactors' treatment performance, and a high load of UV254 would result in significantly reduced removals of UV254 and SUVA254 . Graphical abstract: Highlights: A pilot study employing SA-GAC biofilters was conducted to remove NOM in water. GAC contactors played the dominant role in NOM removal. Middle-upper part was the critical zone in GAC contactors for the removal of NOM. Nutrients supplementation slowed down the DOC breakthrough. The most explanatory water parameter in GAC contactors was UV254 .